Study on the Influence Mechanism of Servo Gain Parameter on the Pitch Deviation Error of Tool Retracting Position - Zhao Chunhua; Liang Zhipeng (Jixie chuandong)
The pitch deviation error of tool retracting position is a critical problem during the machining process of gears with numerical control（NC） shaping machine.After analyzing the influence factors of gear machining accuracy,generating motion out-of-sync is identified as the primary cause of the pitch deviation error in the case of well controlling of geometric accuracy,motion error and positioning precision.In order to reduce the influence of gear installation error and measurement error on gear pitch deviation measurement precision,an online gear precision detection device is designed.According to the influence law of servo gain parameter on the control shaft of servo motor,several orthogonal gear shaping tests are carried out by changing the servo gain parameter.The test results prove that the generating motion out-of-sync of tool retracting position is the primary cause of the pitch deviation error of tool retracting position.Simultaneously,the influence law of servo gain parameter on the pitch deviation error of tool retracting position is analyzed and the corresponding parameter adjustment strategies are proposed.The study provides a new approach to solve the pitch deviation error problem of tool retracting position with NC shaping machine.